INTERNAL VEIN TEXTURE AND VEIN EVOLUTION OF THE EPITHERMAL SHILA-PAULA DISTRICT, SOUTHERN PERU - Chauvet A.; Bailly L.; André A.; Monié P.; Cassard D.; Tajada F.L.; Vargas Ju.R.; Tuduri J. (My University, 2006)
The epithermal Shila-Paula Au–Ag district is characterized by numerous veins hosted in Tertiary volcanic rocks of the Western Cordillera (southern Peru). Field studies of the ore bodies reveal a systematic association of a main E–W vein with secondary N55–60°W veins—two directions that are also reflected by the orientation of fluid-inclusion planes in quartz crystals of the host rock. In areas where this pattern is not recognized, such as the Apacheta sector, vein emplacement seems to have been guided by regional N40°E and N40°W fractures. Two main vein-filling stages are identified. stage 1 is a quartz–adularia–pyrite–galena–sphalerite–chalcopyrite–electrum–Mn silicate–carbonate assemblage that fills the main E–W veins. stage 2, which contains most of the precious-metal mineralization, is divided into pre-bonanza and bonanza substages. The pre-bonanza substage consists of a quartz–adularia–carbonate assemblage that is observed within the secondary N45–60°W veins, in veinlets that cut the stage 1 assemblage, and in final open-space fillings. The two latter structures are finally filled by the bonanza substage characterized by a Fe-poor sphalerite–chalcopyrite–pyrite–galena–tennantite–tetrahedrite–polybasite–pearceite–electrum assemblage. The ore in the main veins is systematically brecciated, whereas the ore in the secondary veins and geodes is characteristic of open-space crystallization. Microthermometric measurements on sphalerite from both stages and on quartz and calcite from stage 2 indicate a salinity range of 0 to 15.5 wt% NaCl equivalent and homogenization temperatures bracketed between 200 and 330°C. Secondary CO2-, N2- and H2S-bearing fluid inclusions are also identified. The age of vein emplacement, based on 40Ar/39Ar ages obtained on adularia of different veins, is estimated at around 11 Ma, with some overlap between adularia of stage 1 (11.4±0.4 Ma) and of stage 2 (10.8±0.3 Ma). A three-phase tectonic model has been constructed to explain the vein formation. Phase 1 corresponds to the assumed development of E–W sinistral shear zones and associated N60°W cleavages under the effects of a NE–SW shortening direction that is recognized at Andean scale. These structures contain the stage 1 ore assemblage that was brecciated during ongoing deformation. Phase 2 is a reactivation of earlier structures under a NW–SE shortening direction that allowed the reopening of the preexisting schistosity and the formation of scarce N50°E-striking S2-cleavage planes filled by the stage 2 pre-bonanza minerals. Phase 3 coincides with the bonanza ore emplacement in the secondary N45–60°W veins and also in open-space in the core of the main E–W veins. Our combined tectonic, textural, mineralogical, fluid-inclusion, and geochronological study presents a complete model of vein formation in which the reactivation of previously formed tectonic structures plays a significant role in ore formation.
Keywords: VEIN SYSTEM; TEXTURE; EPITHERMAL GOLD; BRECCIA; STRUCTURAL CONTROL; PERU